2008
DOI: 10.1111/j.1365-2672.2007.03713.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways that produce volatile sulphur compounds from methionine in Oenococcus oeni

Abstract: Aims:  Determination of pathways involved in synthesis of volatile sulphur compounds (VSC) from methionine by Oenococcus oeni isolated from wine. Methods and Results:  Production of VSC by O. oeni from methionine was investigated during bacterial cultures and in assays performed in the presence of resting cells or protein fractions. Cells of O. oeni grown in a medium supplemented with methionine produced methanethiol, dimethyl disulphide, methionol and 3‐(methylthio)propionic acid. Methional was also detected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Methionol contributes to the raw potato or cauliflower character of wines, can be found in wines at concentrations up to 5 mg/L, and is produced by either S. cerevisiae or Oenococcus oeni through the catabolism of methionine (Moreira et al 2002, Ugliano and Moio 2005, Vallet et al 2008. It contributes to the cooked vegetable aroma of oxidized wines (Escudero et al 2000).…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 99%
“…Methionol contributes to the raw potato or cauliflower character of wines, can be found in wines at concentrations up to 5 mg/L, and is produced by either S. cerevisiae or Oenococcus oeni through the catabolism of methionine (Moreira et al 2002, Ugliano and Moio 2005, Vallet et al 2008. It contributes to the cooked vegetable aroma of oxidized wines (Escudero et al 2000).…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 99%
“…The production of 3-(ethylthio)-1-propanol could be affected by the nitrogen content of the fermented medium (Moreira et al, 2011). Amino acids are the most important nitrogen source for LAB metabolism during wine fermentation, and O. oeni could convert methionine into various VSCs, such as methional and 2-oxo-4-(methylthio)-butyric acid (Vallet et al, 2008). However, Izquierdo et al (2014) reported that O. oeni only played a minor role in the production of VSCs during MLF.…”
Section: Impact Of Inoculation Time Of Malolactic Bacteria On Volatilmentioning
confidence: 99%
“…Vallet et al (2008) found the production of methionol occurred during the exponential growth phase of the LAB, while the production of 3-(methylthio)propionic acid took place during both the exponential and stationary growth phase. These authors also found that methionol and 3-(methylthio)propionic acid production only occur in the presence of methional, which implies that this compound is an important precursor in their production.…”
Section: Volatile Sulphur Compoundsmentioning
confidence: 99%
“…Figure 3 displays the sulphur metabolism in LAB and it is assumed that wine LAB will share some of the characteristics and pathways characterised in other LAB, specifically LAB from the dairy industry (Liu et al, 2008). Vallet et al (2008) proposed the possible pathway by which these compounds are formed by O. oeni. The metabolism of methionine by LAB leads to the formation of methanethiol, dimethyl disulphide, 3-(methylsulphanyl)propan-1-ol (also known as methionol) and 3-(methylsulphanyl)propionic acid.…”
Section: Volatile Sulphur Compoundsmentioning
confidence: 99%